Brazil as an emerging actor in international development cooperation: a good partner for European donors? - Sarah-Lea John de Sousa (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Brazil is an increasingly important actor in international development cooperation. Even though Brazilian international cooperation is relatively small in quantitative terms, the country is increasing it steadily. Brazilian development cooperation is part of its foreign policy and has its origins in the late 1960s, was expanded in the 1980s and 1990s and reinforced again since 2002 as part of the South-South cooperation focus of the Luiz Inacio “Lula” da Silva government. Due to rising percapita income levels Brazil since the 1990s has been not just a recipient but also a provider of development cooperation. Technical cooperation, in terms of capacity building and knowledge exchange, represent the main part, while financial cooperation is still low. The Brazilian Cooperation Agency (Agência Brasileira de Cooperaç\~ao) stresses the following as its overarching objectives: to contribute to the deepening of Brazil's relations with development countries, to extend the exchange and dissemination of technical knowledge, to promote capacity building, and to strengthen the state institutions in development countries. Furthermore, Brazil also aims at projecting its image beyond the region on a global level and at increasing its visibility and impact in international relations and its role as a global actor. In this sense, Brazil has entered into cooperation partnerships with South American, Caribbean and African countries as a means of seeking recognition and support for its global position and for initiatives like its lobbying efforts for United Nations (UN) reform and a permanent seat in the UN Security Council. Although reluctant to accept the Paris Declaration principles which it perceives as being rules imposed by the traditional northern donor countries, Brazil shares key values and ideas with European donors, as in particular the promotion and protection of democracy and human rights in partner countries. In this sense, closer collaboration between Europe and Brazil at both levels, debates on overall coordination, guidelines and rule setting in the field of international development cooperation on the one hand and concrete trilateral projects with other southern developing countries on the other, could be of mutual benefit and are worthy of further exploration. Nevertheless, political and economic interests are also influencing in Brazil's engagement in international development cooperation and should be taken into account when evaluating the potential of Brazil as a partner in international cooperation.
Keywords: 330